(untitled) (Research, Society and Development, 2022)
Brazil is one of the countries that most use herbicides in the world. Its indiscriminate use generates adverse effects on the environment and health. 2,4-Dichlorophenoxyacetic acid is among the 3 most used active ingredients in pesticide in Brazil and can be used in several crops. It can be found in surface and deep soils, sediments of rivers, lakes, seas and groundwater. Bioremediation is a technique that can be efficient to reduce the presence of this residue in the soil by treating polluted areas. Many studies have shown the efficiency of anaerobic degradation of 2,4-D through the metabolism of methanogenic, sulfate-reducing or denitrifying microorganisms. Thus, the present study aimed to analyze the degradation of 2,4-D under different oxidation-reduction conditions. Anaerobic degradation tests were carried out under different conditions, methanogenic, denitrifying and sulfetogenic, using the sediment collected in the Itaipú reservoir. The test results show that there was a variation in the removal of 2.4-D between the different oxidation-reduction media, being 9.26% for the denitrifying condition, 63.33% for the sulfetogenic condition and 100% between the methanogenic conditions. Therefore, the methanogenic medium was the one that presented the best conditions for the remediation of the 2,4-D herbicide under the conditions studied. The results presented may contribute to a more complete analysis of the behavior of this compound in the environment, helping to develop more efficient bioremediation processes.